Highly targeted cholera vaccination campaigns in urban setting are feasible: The experience in Kalemie, Democratic Republic of Congo. - Louis Albert Massing; Soumah Aboubakar; Alexandre Blake; Anne-Laure Page; Sandra Cohuet; Adalbert Ngandwe; Eric Mukomena Sompwe; Romain Ramazani; Marcela Allheimen; Philippe Levaillant; Pauline Lechevalier; Marie Kashimi; et al. (Public Library of Science (PLoS), 2018)
Oral cholera vaccines are primarily recommended by the World Health Organization for cholera control in endemic countries. However, the number of cholera vaccines currently produced is very limited and examples of OCV use in endemic countries, and especially in urban settings, are scarce. A vaccination campaign was organized by Médecins Sans Frontières and the Ministry of Health in a highly endemic area in the Democratic Republic of Congo. This study aims to describe the vaccine coverage achieved with this highly targeted vaccination campaign and the acceptability among the vaccinated communities.We performed a cross-sectional survey using random spatial sampling. The study population included individuals one year old and above, eligible for vaccination, and residing in the areas targeted for vaccination in the city of Kalemie. Data sources were household interviews with verification by vaccination card. In total 2,488 people were included in the survey. Overall, 81.9% (95%CI: 77.9-85.3) of the target population received at least one dose of vaccine. The vaccine coverage with two doses was 67.2% (95%CI: 61.9-72.0) among the target population. The vaccine coverage was higher during the first round (74.0, 95%CI: 69.3-78.3) than during the second round of vaccination (69.1%, 95%CI: 63.9-74.0). Vaccination coverage was lower in male adults. The main reason for non-vaccination was to be absent during the campaign. No severe adverse events were notified during the interviews.Cholera vaccination campaigns using highly targeted strategies are feasible in urban settings. High vaccination coverage can be obtained using door to door vaccination. However, alternative strategies should be considered to reach non-vaccinated populations like male adults and also in order to improve the efficiency of the interventions.